2020
DOI: 10.26434/chemrxiv.13221119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Repurposing of Ursodeoxycholate and Chenodeoxycholate as Lead Candidates Against SARS-Cov2-Envelope Protein: A Molecular Dynamics Investigation

Abstract: Drug repurposing is an apt choice to combat the currently prevailing global threat of COVID-19, caused by SARS-Cov2 in absence of any specific medication/vaccine. The present work attempts to computationally evaluate binding affinities and effect of two widely used surfactant drugs i.e. chenodeoxycholate (CDC) and ursodeoxycholate (UDC) with the envelope protein of SARS-Cov2 (SARS-Cov2-E) using homology modelling, molecular docking and molecular dynamics simulations. A good quality homo-pentameric structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Yadav et al demonstrated by computational methods that CDC and UDC can stably bind to the transmembrane domain of SARS-CoV-2 E protein through hydrogen bond and other interactions to form a thermodynamically stable complex, in which T30 residue is the key residue to bind to CDC and UDC. [87] CDC and UDC can also destroy the hydrogen bond between adjacent chains to loose the structure of E protein pentamer and allow a large number of CDC molecules to enter the membrane. In conclusion, these two drugs can inhibit the survival of SARS-CoV-2 virus by destroying the structure of E protein and promoting the entry of inhibitors into virus-infected cells.…”
Section: Pharmacology Of Sars-cov-2 E Proteinmentioning
confidence: 99%
“…Yadav et al demonstrated by computational methods that CDC and UDC can stably bind to the transmembrane domain of SARS-CoV-2 E protein through hydrogen bond and other interactions to form a thermodynamically stable complex, in which T30 residue is the key residue to bind to CDC and UDC. [87] CDC and UDC can also destroy the hydrogen bond between adjacent chains to loose the structure of E protein pentamer and allow a large number of CDC molecules to enter the membrane. In conclusion, these two drugs can inhibit the survival of SARS-CoV-2 virus by destroying the structure of E protein and promoting the entry of inhibitors into virus-infected cells.…”
Section: Pharmacology Of Sars-cov-2 E Proteinmentioning
confidence: 99%